Optimized two‐dimensional gel electrophoresis in an alkaline pH range improves the identification of intracellular CFDA‐cisplatin‐protein adducts in ovarian cancer cells. Issue 12 (16th May 2018) - Kotz, Sandra; Kullmann, Maximilian; Kalayda, Ganna V.; Dyballa‐Rukes, Nadine; Jaehde, Ulrich; Metzger, Sabine
Abstract: Intracellular binding of cisplatin to proteins has been associated with acquired resistance to chemotherapy. In our previous study we established an analytical method for the identification of intracellular cisplatin‐binding proteins. The method used a fluorescent carboxyfluorescein‐diacetate‐labeled cisplatin analogue (CFDA‐cisplatin), two‐dimensional gel electrophoresis (2DE) and mass spectrometry, which allows detecting and identifying intracellular CFDA‐cisplatin‐containing protein adducts in the acidic pH range (pH 4–7). Based on this analytical method we extended the identification of intracellular cisplatin‐protein adducts to the alkaline pH range (pH 6–10) giving chance to discover new important binding partners. 2DE analysis of alkaline proteins is challenging due to the difficult separation of basic proteins during the isoelectric focusing (IEF). The establishment of an optimized IEF protocol for basic proteins enabled us to identify several intracellular CFDA‐cisplatin‐binding proteins including enzymes of the glucose and serine metabolism like alpha enolase and D‐3‐phosphoglycerate 1‐dehydrogenase.